Andapung / Wan Emilda Izhany Wan Noor Afandi ... [et al.] - Wan Noor Afandi, Wan Emilda Izhany; Mohd Sabri, Siti Nurnadhira; Abd Hafiz, Muhammad Adam Hakimi; Ahmad, Norfazillah (2024)
This design incorporates the fishbone's organic elegance to represent resilience, strength, and connectivity. Drawing inspiration from nature’s efficiency, it emphasizes structural integrity and spatial flow. The layout is inspired by the dynamic geometry of the fishbone, which depicts easy movement and flexible use of space. We adopt its sustainable philosophy, optimizing use while reducing our environmental impact. Similar to the robust skeleton of a fish, this concept encourages lifespan and environmental harmony. Our aim is to design architectural environments that exude life, purpose, and eternal beauty by combining form and function.